Human Resources Oriented: Kerangka Strategis Pengembangan MAN Insan Cendekia Kendari - Hartin Hartin (Shautut Tarbiyah, 2020)
This article aims to provide an overview of the direction of the development of MAN IC that focuses on the formation of high quality Human Resources. The aspects explored are the process of preparing future leaders, the development of students' interests and talents, the competence of educators and education personnel, and governance of madrasas. Qualitative research is used to answer the dimensions of the study above, through a process of interviews, observations, and document review. Data were analyzed through the stages of reduction, presentation, and drawing conclusions. The results showed that the process of preparing prospective leaders is an important part of the education and learning system at MAN IC Kendari, which is contained in activities that stimulate leadership and build independence, both curricularly and extracurricularly. Therefore, the development of students' interests and talents is a must, as a vehicle for leadership readiness training. Teachers' readiness is realized by learning interactions in the classroom that are relevant to the needs of students, as well as the ability to assist activities outside the classroom. Likewise educational staff, synergistically supporting the learning activities. MAN IC climate can be realized because of good organizational governance. Keywords: Human Resources, Strategies, Madrasa Governance